Diversity, taxonomy and conservation status of horseshoe bats (Chiroptera: Rhinolophidae) in Vietnam - Thanh, Hoang Trung; Son, Nguyen Truong; Sang, Nguyen Van; Thai, Dinh Nho; Hoang, Nguyen Huy; Tu, Vuong Tan; Huan, Nguyen Xuan; Thong, Vu Dinh (Academia Journal of Biology, 2017)
Over the recent years, results from investigation into the family Horseshoe bats (Rhinolophidae) indicated that the taxonomic status of many species in Vietnam is still unclear. Having studied on 1,140 specimens of the genus Rhinolophus, we confirm that Vietnam is a home to 20 horseshoe bat species. Remarkably, our study results obtained 6 unusual forms belonging to 5 species complexes: R. affinis, R. malayanus, R. thomasi, R. paradoxolophus and R. marshalli. These froms differ from the described species in all morphology, echolocation and genetics. Conservation status of 4 rarely documented species of horseshoe bats from Vietnam: R. thomasi, R. paradoxolophus, R. osgoodi and R. luctus is also given in this paper. Citation: Hoang Trung Thanh, Nguyen Truong Son, Nguyen Van Sang, Dinh Nho Thai, Nguyen Huy Hoang, Vuong Tan Tu, Nguyen Xuan Huan, Vu Dinh Thong, 2017. Diversity, taxonomy and conservation status of horseshoe bats (Chiroptera: Rhinolophidae) in Vietnam. Tap chi Sinh hoc, 39(2): 174-184. DOI: 10.15625/0866-7160/v39n2.9213 *Corresponding author: thanhht_ksh@vnu.edu.vn Received 11 February 2017, accepted 16 February 2017